Predictive Analysis For Credit Card Transaction Management System Based On Process Mining Techniques - et. al., C. Rohith Bhat, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
To attract the customers, business partners and organization, we need to execute processes with high consistency for achieving predictable quality. Now a day's many companies have been focused to improve Business process automation technologies .It can be used to improve the efficiency of both internal processes and customer services. Business process should be performed more effectively with good design process. Most of the organizations are selling their products ,services, pay, purchase of materials and submit their tax through information systems. These systems are used to record information about process execution on event logs .Data mining techniques are used to describe cash payments based on transactions. in this paper for In this paper process mining techniques are used to improve credit card transaction process. Model of the credit card transaction process is described with design constraints and events. In this paper proposed algorithm is introduced to get optimal transaction of credit card transaction process